Una respuesta a la ‘dificultad contramayoritaria’ a partir de las ‘virtudes pasivas’ de los jueces (2014)
In the first part of this paper describes some general assumptions to understand the problem of the countermajoritarian difficulty of Alexander Bickel. Subsequently, it is come to explain the response to the countermajoritarian difficulty where judges are an auxiliary democracy through judicial review. Next, it will be shown the image of prestige of the courts and the educational function. This argument says that judges are not a countermajoritarian power, by contrast, are supporting democracy. Finally, it will be argued that DCM Bickel involves the creation of an inter-institutional dialogue, because the judges based on mature cases are responding to the demands of society.